(untitled) (TAMADDUN NURI JURNALI, 2024)
The article presents new information on the history of the study of the Kyzlartepa monument located in the central part of Sogda and what its function was. In the research carried out at the Kyzlartepa monument, the monument is closed in the form of a corridor and a dome-shaped roof. There are coins and ceramic pieces from the early middle ages. The monument was interpreted by Lebedova as a summer residence of Sugdian ikhshids. As a result of the latest research, it is possible that the monument was the residence of a customs house or a Sogdian zamindar. The architectural structure (wall, floor, raw brick), remains and archaeological objects found in the excavated area of ​​the Kyzlartepa monument show that the complex belongs to the IV-VIII centuries.